Balanced Nutrition Intake for Toddlers with the Use of Local Food as Stunting Prevention - Purnama, Dadang; Witdiawati; Zaenal Muttaqin (LPPM Universitas Muhammadiyah Tasikmalaya, 2025)
Stunting is one of the main health problems in Indonesia, with a high prevalence, especially in rural areas. Stunting can hinder children's physical growth and cognitive development, which has implications for their health. Factors such as maternal education level, family income level, and feeding practices in toddlers are known to have a significant relationship with the incidence of stunting. Therefore, this service activity is carried out to increase the knowledge of mothers under five related to balanced nutrition based on local food as stunting prevention. The method used in the service is counseling and demonstration of making additional food for toddlers with the use of local food ingredients of moringa leaves. The participants of the activity were 21 mothers who have children under five and 7 pregnant women who are in 2 RWs in Sukamentri Village, Garut Kota District, Garut Regency. Result. There was an increase in the knowledge of mothers who have children under five related to balanced nutrition from local food sources with an average pre-test score of 65.8 to 82.3 for the average post-test score. Therefore, this activity was carried out to increase knowledge related to balanced nutrition in toddlers based on local food as stunting prevention in the form of feeding practices for toddlers with stunting incidents in Sukamentri Village, Garut Kota District, Garut Regency.